A blockchain-based service composition architecture in cloud manufacturing. Issue 7 (2nd July 2020) - Yu, Chunxia; Zhang, Luping; Zhao, Wenfan; Zhang, Sicheng
ABSTRACT: Cloud manufacturing is a promising rising paradigm in which geographically distributed manufacturing resources are exposed as services in the cloud platform. The task of cloud manufacturing is to provide manufacturing resources as services to fulfil users' demands. However, in existing cloud manufacturing architecture all the information is possessed by the platform operator, and the management of manufacturing services is highly centralised. It is firmly believed that decentralisation and elevating information transparency can help increase the operational performance. Blockchain is such a technology that distributes transactions information to a peer-to-peer network such that information is fully shared and unchangeable by partial peers. This paper proposes a blockchain-based cloud manufacturing architecture to enhance information transparency and decentralisation. The proposed platform is responsible for exposing manufacturing resources and wrapping them as services. Manufacturing services can be purchased by any user accessing to the platform. The blockchain is used to intermediate the service composition and record transaction results. Moreover, a quality of service (QoS) aware service composition model is proposed in the blockchain-based cloud manufacturing. A particle swarm optimisation (PSO) is proposed to solve the model. Finally, simulations are done to provide an application of the service composition in blockchain-based cloud manufacturing.